Identification of soluble APO-1 in supernatants of human B- and T-cell lines and increased serum levels in B- and T-cell leukemias - Knipping, Eckart; Debatin, Klaus-Michael; Stricker, Kirstin; Heilig, Bernhard; Eder, Astrid; Krammer, Peter H. (Blood, 1995)
The cell-surface protein APO-1 is a member of the nerve growth factor (NGF)/tumor necrosis factor (TNF) receptor superfamily. APO-1 mediates apoptosis in susceptible cells upon stimulation with the monoclonal antibody anti-APO-1 or upon binding of its natural ligand. Soluble receptors had previously been identified for most members of the NGF/TNF receptor superfamily. Recently, a soluble form of APO-1 (sAPO-1) was described. We established a sandwich enzyme-linked immunosorbent assay to detect sAPO-1 in culture supernatants of human cell lines and in human sera. sAPO-1 was found in culture supernatants of different human B- and T-cell lines. Molecular weights of sAP0-1 and membrane APO-1 were similar. In addition, in comparison to healthy donors, sera from patients with different highland low-grade malignant B- and T-cell leukemias and lymphomas contained increased levels of sAP0-1. These findings may have implications for the growth of leukemias and the diagnostic monitoring of individual patients.